2015
DOI: 10.5430/jha.v5n1p29
|View full text |Cite
|
Sign up to set email alerts
|

Population aging and physician maldistribution: A longitudinal study in Japan

Abstract: Background: Over the past two decades, population aging and the introduction of the new postgraduate medical education program in 2004 have impacted on the geographic maldistribution of physicians in Japan. The purpose of this study was to evaluate recent changes in physician distribution across municipalities from 1996 to 2012 using Gini coefficients and to clarify the impact of the new medical education program on physician distribution. Methods: We extracted the number of physicians classified by type of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Similarly, a study conducted in China examined the Gini coefficient of CT scan centers in 2006 and 2009, which yielded values of 0.14 and 0.15, respectively [ 25 ]. Likewise, a study conducted in Japan demonstrated a significant disparity in the geographical distribution of diagnostic imaging devices, which aligns with the findings of the present study [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, a study conducted in China examined the Gini coefficient of CT scan centers in 2006 and 2009, which yielded values of 0.14 and 0.15, respectively [ 25 ]. Likewise, a study conducted in Japan demonstrated a significant disparity in the geographical distribution of diagnostic imaging devices, which aligns with the findings of the present study [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…The unequal distribution of healthcare professionals, particularly doctors, has emerged as a growing concern in the global healthcare sector [ 4 ]. For example, in Japan, Matsumoto et al found a significant increase in the Gini coefficient after 2006, indicating an inappropriate distribution of doctors [ 5 ]. Moreover, the inequality ratio in the allocation of specialist services exceeds that of general practitioners (GPs) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, studies by Mosadeghrad, Ünal, Hazarika, and Toyabe have described the distribution of physicians as unfair in different countries. [ 21 22 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the supply and demand as well as the geographical maldistribution of physicians in Japan [6][7][8][9][10][11][12][13], but there only few studies have empirically analyzed the data on the situation of obstetricians/gynecologists [1,3,14]. Furthermore, regarding geographical maldistribution of obstetricians/gynecologists, there is only one estimation of the index of geographical physician maldistribution by the Study Group on the Supply and Demand of Medical Workers of the MHLW [15].…”
Section: Introductionmentioning
confidence: 99%